2013
DOI: 10.1039/c3cc47338d
|View full text |Cite
|
Sign up to set email alerts
|

Reversible oxidation of a water-soluble tellurophene

Abstract: Oxidation of a novel water-soluble tellurophene [2,5-tellurophene-bisphenoxy(octaethylene glycol monomethyl ether)] by peroxide is electrochemically reversible. This tellurophene can also be oxidized by self-photosensitized singlet oxygen in an aqueous solution. The oxidized tellurophenes are studied by optical absorption spectroscopy, (1)H NMR, and electrochemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…The formation of 5 is attributed to the transesterification during purification of crude products via column chromatography, where the eluent contains formic acid. Along with previous report, 53,54 the present result further indicates that electrondonating substituents are essential for the tellura-BV oxidation.…”
Section: Chemical Science Accepted Manuscriptsupporting
confidence: 91%
See 1 more Smart Citation
“…The formation of 5 is attributed to the transesterification during purification of crude products via column chromatography, where the eluent contains formic acid. Along with previous report, 53,54 the present result further indicates that electrondonating substituents are essential for the tellura-BV oxidation.…”
Section: Chemical Science Accepted Manuscriptsupporting
confidence: 91%
“…[46][47][48][49][50][51][52] Recently, Seferos's group performed the oxidation of tellurophenes with peroxides and found that they can be converted to various states including dihydroxy tellurophenes, and telluroxide and tellurone (Scheme 1b). 53,54 Further oxidation of tellurophene Te-oxide with mCPBA resulted in ring cleavage to form but-2ene-1,4-dione instead of tellurinate lactone. 53 In BV oxidation, the migration step is rate-determining in most cases and electron-donating substituents in the migrating group will promote the rearrangement [8][9][10]55 Herein, with the intention to explore hetero-BV oxidation, we chose the tellurophene-embedded and electron-rich polycycles as substrates.…”
Section: Introductionmentioning
confidence: 99%
“…A similar reversible oxidation wave was not observed for 3 , which has an oxidation potential of 1.16 V versus the Ag/Ag + reference. The irreversible oxidation is possibly attributable to the formation of dihydroxyl tellurophene or the telluroxide species, which are hard to reduce . The oxidation potential shifts to a more negative value for 3 , which indicates that the incorporation of Te results in more facile oxidation than that observed for S and Se.…”
Section: Methodsmentioning
confidence: 90%
“…28 Tellurophenes possess interesting photophysical properties and have been investigated as light harvesting agents for solar cell applications and in materials chemistry. 28 Tellurophenes possess interesting photophysical properties and have been investigated as light harvesting agents for solar cell applications and in materials chemistry.…”
Section: Tellurophenes: Synthesis and Stabilitymentioning
confidence: 99%